Energy use policies and carbon pricing in the UK - Arun Advani; Samuela Bassi; Alex Bowen; Sam Fankhauser; Paul Johnson; Andrew Leicester; George Stoye (Institute for Fiscal Studies (IFS), 2013)
This report, funded by the Esmée Fairbairn Foundation and the Economic and Social Research Council (ESRC), examines the effect of UK government policies on energy use and carbon pricing. The work was undertaken by researchers from the ESRC Centre for the Microeconomic Analysis of Public Policy at the Institute for Fiscal Studies (IFS), in collaboration with the ESRC Centre for Climate Change Economics and Policy and the Grantham Research Institute on Climate Change and the Environment at the London School of Economics and Political Science (LSE). The report analyses and assesses: *the rationale and objectives of energy policy; *the current policy landscape faced by UK energy users; *how current and future policy has led to inconsistencies in the implicit carbon prices faced by different users; *potential ways in which to improve policy affecting domestic and business energy users.
Keywords: 330